Effect of convalescent plasma as complementary treatment in patients with moderate COVID‐19 infection. Issue 2 (9th January 2022) - Baldeón, Manuel E.; Maldonado, Augusto; Ochoa‐Andrade, Miguel; Largo, Carolina; Pesantez, Mónica; Herdoiza, Marco; Granja, Gerardo; Bonifaz, Marco; Espejo, Hugo; Mora, Francisco; Abril‐López, Patricio; Armijo, Lady Karen Robles; et al.
Abstract: Introduction: South America is one of the regions most affected by the COVID‐19 pandemic. Specific and affordable treatments are needed to treat SARS‐CoV‐2 infection. Evidence regarding the use of convalescent plasma in COVID‐19 patients is still limited. We compared the safety and efficacy of COVID‐19‐convalescent plasma administration as a complement to standard treatment in the early management of patients with moderate SARS‐CoV‐2 infection. Methods: We carried out a random double blinded, placebo‐controlled trial that compared standard treatment plus convalescent plasma (CP) or plus non‐convalescent plasma in the management of COVID‐19 patients. The main outcome was survival and secondary endpoints included: length of hospitalisation (LOH), days from treatment to discharge, time to clinical improvement or death within a 28‐day period, and adverse reactions to treatment. Results: Administration of CP with antibodies against SARS‐CoV‐2 did not affect patient survival, RR = 1.003, 95% CI (0.3938, 2.555). These results led to terminate the RCT prematurely. However, early treatment of COVID‐19 patients with CP tended to decrease the LOH while the delay in CP treatment was associated with longer hospitalisation. In addition, delay in CP treatment negatively affected the recovery of the respiratory rate. Conclusion: Use of CP for the treatment of COVID‐19 patients is safe and its early use can decrease the LOH and improve respiratory function. Early administration of antibody‐rich CP could contribute to decrease the negative impact of COVID‐19 pandemic in patients with impaired immune response.